Identifying the Green Supply Chain for Environmental Sanitation Management in Banda Aceh, Indonesia - Rusli Yusuf; Maimun Maimun; Sanusi Sanusi; Jumadil Saputra; Sofyan A. Gani (International Journal of Supply Chain Management, 2020)
Abstract. This study aims to identify the effect of green supply chain management on environmental sanitation management in Banda Aceh. It caused by a high level of diversity and population density and circular migration in these city. This quantitative study conducted to 3 districts along case, namely densest, most diverse population and circular migration characteristics. A total of 400 respondents spreading in 3 districts were participated in this study. The result of the study shows that the behavior of Banda Aceh people is categorized as standard. Furthermore, the awareness level of Banda Aceh people on environmental sanitation management is categorized as good. Meanwhile, Green supply chain strategy and people awareness are caused by increased population growth due to massive urbanization and high birth rate. However, the existence of public facilities (such as garbage dump, etc.) and people's awareness about the environment is still lacking. Environmental sanitation management still needs the government to play a key role in improving infrastructures such as green supply chain for garbage dump, clean water tank, waste treatment facilities for residual waste, organic and inorganic waste as well as continuous socialization related to environmental sanitation management issues that can influence behavioral change and emerge high awareness from the community towards a healthier life in accordance with the objectives of sustainable development goals.